2020
DOI: 10.1111/gwao.12573
|View full text |Cite
|
Sign up to set email alerts
|

What are men's roles and responsibilities in the feminist project for gender egalitarianism?

Abstract: The #MeToo and the Time's Up movements have captured the urgency to address systemic manifestations of sexism, patriarchy, and misogyny in all aspects of society. Among the myriad discourses that have been catalyzed by these contemporaneous movements includes one related to the role of men in achieving gender egalitarianism. Men are allocated unearned privilege associated with being a man in a culture that is inherently phallogocentric. This fact alone charges men with the responsibility to account for the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…Thousands of Palestinians protested, and the PSF's intelligence officers reportedly dragged protesters in the streets, harassing women, stealing their phones, and threatening to publish intimate pictures on social media (Alijla, 2021). Violence and surveillance, enacted literally or discursively, and manifested in digital or physical forms, are routinely exercised over Palestinian citizens (Prasad, 2019). This is the context in which our women activists' stories are situated.…”
mentioning
confidence: 99%
“…Thousands of Palestinians protested, and the PSF's intelligence officers reportedly dragged protesters in the streets, harassing women, stealing their phones, and threatening to publish intimate pictures on social media (Alijla, 2021). Violence and surveillance, enacted literally or discursively, and manifested in digital or physical forms, are routinely exercised over Palestinian citizens (Prasad, 2019). This is the context in which our women activists' stories are situated.…”
mentioning
confidence: 99%
“…This shows that the subaltern nature of women in the political system has been much confirmed [31]. The Covid-19 pandemic has shown that its impact has been unparallel in the history of mankind because it has thoroughly affected all sectors of human endeavour, more also women have been severely affected by indices available [32][33][34][35][36][37]. It is therefore important that any recovery plan should address the gender impact of this pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…I got some very interesting responses, though it was quite clearly an uncomfortable question for them to answer. Several of them began their narrative by saying something to the effect of: ‘I’m not sure if I should be answering this question; I don’t want to take up the space to which I’m not entitled.’ I should say that each of these men are very progressive, enlightened, intellectually gifted (see Prasad et al, in press). I would like to pose this same question to you.…”
Section: Interviewmentioning
confidence: 99%